PRODUCTION OF ZINC ANODES AT THE PILOT-SCALE PRODUCTION ITM NAN OF BELARUS - E. I. Marukovich; E. F. Baranovski; V. M. Iljushenko; G. P. Korotkin (Литьë и металлургия, 2005)
The production of precision-sized zinc anodes for metallurgy and machine-building under the technology, developed by ITM NAN of Belarus is described.